Pengaruh Penggunaan Gadget terhadap Perkembangan Karakter Peduli Sosial pada Anak Usia 4-5 Tahun di Taman Kanak-Kanak Adetia - Nanda Yuliantika; Humaidah Br. Hasibuan; Raisah Armayanti Nasution (Institut Nalanda, 2024)
This research is quantitative research and an ex-post-facto approach, this research involves collecting data through questionnaires aimed at parents and direct observation of young children. The population numbered 15 children. So the formulation of the problem in this research is